How I Grow: Months Three and Four - Millie Ferrer; Keith Gouin (EDIS)
At this age babies often enjoy splashing in the tub or kicking their feet in the air as they lay on their back. Play is essential for a baby’s healthy development. Through play, babies learn about themselves and the world around them. A loving parent is the best toy any baby can have. By creating a stimulating, playful environment, parents help their infant develop physically, socially, emotionally, and intellectually. This document is FCS2218, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, University of Florida, IFAS, Gainesville, FL 32611. First published: August 2003.